2008
DOI: 10.1021/cm7035234
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Path of Oxide Ions in an Apatite-Type Ionic Conductor La9.69(Si5.70Mg0.30)O26.24

Abstract: Densities of coherent-scattering lengths in oxide-ion conductor La9.69(Si5.70Mg0.30)O26.24 with an apatite-type structure (space group P63/m) have been determined by a whole-pattern fitting approach based on the maximum-entropy method (MEM) using neutron powder diffraction data measured at 25 and 1558 °C. The Rietveld refinement suggested an interstitial oxygen (O5) atom site (12i; x, y, z; x ≈ 0, y ≈ 0.22, z ≈ 0.65) at the periphery of the hexagonal axis. The oxide ions located at 2a (O4) and 12i (O3) sites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
88
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 44 publications
11
88
2
Order By: Relevance
“…The high conductivity was first observed by one of the authors [1,2]. Although the conduction mechanism has been extensively investigated [8][9][10][11][12], it has not been fully understood. Apatite has three kinds of sites for oxide ions in its structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high conductivity was first observed by one of the authors [1,2]. Although the conduction mechanism has been extensively investigated [8][9][10][11][12], it has not been fully understood. Apatite has three kinds of sites for oxide ions in its structure (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ali showed that the oxide-ion migration is mainly caused by a vacancy mechanism in the isolated (O4) oxide ion along the c-axis. However, the migration of oxide ion on theO3-O5-O4 path is significant with increasing temperature, where O5 is the interstitial oxide ion which is produced by the addition of MgO to La-apatite and is present between O3 and O4 ions [9]. Computer simulations for oxygen-excess La9.67(SiO4)6O2.5 apatite predicted that the presence of oxide ions at interstitial sites near the SiO4 tetrahedra form pseudo-"SiO5" units [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…For the silicates it has been shown that oxygen excess in the range, 0 ≤ x ≤ 0.5 is possible, while higher oxygen content, 0 ≤ x ≤ 1.0 has been achieved for the germanates [13,18,20,21]. For the silicate series, the exact location of extrastoichiometric oxygen, x, has attracted some controversy, with reports of interstitial sites close to the SiO4 tetrahedra, while in other studies, mobile oxygen at the centre of the channels has been claimed [4,8,9,10,12,13,23,27,35,36]. For the germanates, the situation appears more clearcut, with computer modeling, neutron diffraction and Raman studies indicating occupancy by oxygen sites close to the GeO4 tetrahedra leading to the formation of five coordinate Ge [10, 20-22, 37, 40].…”
Section: Introductionmentioning
confidence: 99%
“…In 80) They refined the structure parameters using a structure model with P6 3 /m. A feature of their results was that anisotropic thermal displacements of the La1(4f ) and La2(6h) sites were expanded along the c-axis and the ab plane, respectively, at room temperature.…”
Section: Crystal Structure Model After the Discovery Of Oxygen-ion Comentioning
confidence: 99%